Purificación parcial de péptidos bioactivos con actividad antihipertensiva y antitrombótica de una leche comercial fermentada con Lactobacillus casei Shirota y Streptococcus thermophilus - Domínguez González, Karina Nataly (Universidad Autónoma Metropolitana, 2014)
The aim of this paper is to show that the fermented milk product by L. casei Shirota and Streptococcus thermophilus (Sofúl®) has peptides that are able to inhibit the fibrin clot formation by thrombin and/or to inhibit angiotensin converting enzyme (ACE). The commercial fermented product contains agar, carrageenan and gelatin, so a step of purification was necessary to prepare an extract free of gums. Eight peptides, which were purified by reversed phase and molecular exclusion chromatography, showed inhibitory activity of ACE and six showed antithrombotic activity. Those that demostrate the highest specific activity were tested under enzymatic digestion in vitro, although six peptides were not apparently modified by the gastric enzymes, only three of them retained its biological activity. Peptides 5 and 6 show the ACE inhibitory activity and antithrombotic. The peptide 5 had an inhibition efficiency ratio of ACE (IER) and antithrombotic activity of 21.3 % ± 1.6 % and 34.8 ± 14.3 respectively. Peptide 6 had an inhibition efficiency ratio ACE 24.6 % ± 0.1 and antithrombotic activity of 59.3 % ± 15.2. Furthermore, peptide 12 showed antithrombotic activity, which was retained after digestion with pepsin and trypsin 10.13 ± 33.82 %. This research is just one approach to multifunctional peptides whose bioactivities could affect positively the cardiovascular system through the consumption of fermented milk containing these peptides.; El objetivo de este trabajo fue determinar si el producto lácteo fermentado por Lactobacillus casei Shirota y Streptococcus thermophilus (Sofúl®) posee péptidos capaces de inhibir la formación del coágulo de fibrina por la trombina y/o inhibir a la enzima convertidora de angiotensina (ACE). El Sofúl está adicionado con agar, carragenina y grenetina por lo que para su purificación, fue necesario preparar un extracto libre de gomas. Ocho péptidos purificados por cromatografía de exclusión molecular y fase reversa presentaron actividad inhibidora de la ACE y 6 presentaron actividad antitrombótica. Aquellos que presentaron la mayor actividad específica, fueron probados in vitro bajo condiciones de digestión enzimática, aunque seis péptidos no fueron aparentemente modificados por las enzimas gástricas, solo tres de ellos conservaron su actividad biológica. Los péptidos 5 y 6 mostraron tanto actividad inhibitoria de la ACE como actividad antitrombótica. El péptido 5 tuvo intervalos de eficiencia de inhibición especifica de la ACE y de actividad específica antitrombótica de 21.3 % ± 1.6 y 34.8 % ± 14.3 respectivamente. El péptido 6 inhibió la ACE 24.6 % ± 0.1 y presentó una actividad antitrombótica de 59.3 % ± 15.2. Además, el péptido 12 mostró actividad antitrombótica de 33.82 % ± 10.13 la cual fue conservada después de la digestión con pepsina y tripsina. Este trabajo es solo un acercamiento al estudio de péptidos multifuncionales cuyas bioactividades podrían afectar positivamente al sistema cardiovascular a través del consumo de leches fermentadas que contengan estos péptidos.